Copy number variations at the Rhg1 locus and their relationship with resistance to soybean cyst nematode (Heterodera glycines) - Dinesh Poudel; Guiping Yan; Carrie Miranda; Gustavo Fernando Kreutz; Intiaz Amin Chowdhury (Frontiers in Plant Science)
Soybean cyst nematode (SCN, Heterodera glycines) is a devastating pest affecting soybean production worldwide. Host resistance is one of the primary practices used to manage SCN. The Rhg1 locus contributes to the strong and effective SCN resistance, with resistance levels predominantly governed by copy number variations (CNVs) and, to lesser extent, sequence variations. This study assessed the host resistance of 100 soybean breeding lines to SCN populations HG type 2.5.7 (S1) and HG type 7 (S2). Two controlled growth chamber experiments involved inoculating plants with 2,000 SCN eggs and juveniles, followed by counting SCN white females and calculating the female index (FI) to classify resistance responses. To determine CNVs at the Rhg1, a SYBR Green-based quantitative PCR (qPCR) assay was optimized and validated using 12 soybean accessions with known copy numbers. The qPCR assay demonstrated 94.36% efficiency for the target gene at Rhg1 locus, Glyma18g02590, with copy number detected by the assay correlating strongly (r=0.994) with whole genome sequencing data in previous study. Copy number of each line was determined using 2−ΔΔCq method relative to Williams 82 (single copy) and correlated with the resistance response. One line, ND20-16996(GT) was resistant (FI<10%) to S2 in both runs, while none were resistant to S1. Copy number among the breeding lines ranged from 1 to 11, with higher copy numbers correlating negatively with female index, indicating greater resistance. The breeding lines with copy number ≥ 9 were either resistant or moderately resistant to S2, and mostly moderately resistant to S1, with few being moderately susceptible (FI=30 to <60%). The lines with low copy numbers (≤3) were mostly susceptible (FI≥60%) to S1, while moderately susceptible or susceptible to S2. These results show the importance of Rhg1 CNVs in determining levels of SCN resistance and selecting resistant soybean lines.